The Association between Ovarian Hyperstimulation Syndrome and Pregnancy Complications following Fertility Treatments - Vainer-Rotbart, Shirah; Sheiner, Eyal; Harlev, Avi; Bar, Guy; Levy, Amalia (American Journal of Perinatology, 2021)
Objective This study was aimed to assess the association between ovarian hyperstimulation syndrome (OHSS) and pregnancy complications among women who conceived following fertility treatment.Study Design A retrospective population-based cohort study, including all singleton deliveries of patients conceived following ovulation induction (OI) or in vitro fertilization (IVF) between 1988 and 2016, was conducted. All births occurred in a single tertiary medical center. A comparison was performed between deliveries of women who had experienced OHSS at early gestation and subsequently had a pregnancy and women without OHSS. Women lacking prenatal care, multiple gestations, and stillbirths were excluded from the analyses. A multivariable logistic regression model was used to control for confounders.Results During the study period, 351,373 deliveries met the inclusion criteria, of which 6,748 were deliveries of infants who were conceived by either IVF or OI. Of this study population, 105 cases (1.6%) composed the exposed group, that is, women who had experienced OHSS with a subsequent live birth. In the multivariate analyses, after controlling for confounders, OHSS was not found as an independent risk factor for preeclampsia, gestational diabetes mellitus (GDM), intrauterine growth restriction (IUGR), preterm delivery (both <37 and <34 weeks), low birth weight (LBW), very LBW (VLBW), small for gestational age (SGA), and caesarean delivery. In a subanalysis conducted solely on the IVF population, similar results were found, aside from the association between OHSS and preterm delivery before 34 weeks of gestation which was statistically significant (adjusted odds ratio [AOR] = 2.3 95% confidence interval [CI]: 1.0–5.3, p = 0.049).Conclusion In our population, OHSS was not found as a risk factor for adverse pregnancy and perinatal outcome. In IVF patients, OHSS is a risk factor for preterm delivery before 34 weeks of gestation.Key Points
Keywords: ovarian hyperstimulation syndrome; pregnancy complications; assisted reproductive technology; in vitro fertilization; ovulation induction